Preparation of Sb Doped Nano SnO2/Porous Ti Electrode and Its Degradation of Methylene Orange. Issue 6 (June 2015) - Guangzhong, Li; Gang, Li; Hui, Wang; Changshu, Xiang; Jiandong, Zhuang; Qian, Liu; Huiping, Tang
Abstract Sb doped nano SnO2 coating electrode was prepared on the porous Ti by a simple thermal decomposition method and then its electrochemical property for degradation of methylene orange was also investigated. SEM and XRD measurements results show that an integrative and crackless coating layer on porous Ti substrate can be obtained. The crackless coating surface is composed of Sb doped SnO2 nanoparticles with a size range from 80 nm indicates to 230 nm. HRTEM test suggests that these SnO2 nanoparticles consist of coating grains with 5∼6 nm. Intensified life time test indicates that SnO2/porous Ti electrode has a longer service life time than the coatings on dense titanium plate. Moreover, the as-prepared Sb doped SnO2/porous Ti electrode can degrade the methylene orange with 100 mg/L concentration into that with 8 mg/L, which reveals that the electrode has a strong electrochemical ability to degrade organic pollutants. A simple surface treatment of porous Ti for organic pollutants degradation was presented in the paper, showing its great application potential in the area of pollutants degradation.